Arm Span to Height Ratio in Relation to Severity of Dyspnea - Muhamad, Amar K.; Sultan, Kassim M.; Al-Juboury, Adnan M.; Al_Nuamii, Salman H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Arm span is the closest physiologic measurement to standing height. Increased arm span to standing height ratio, which indicates a possible loss of height, due to aging, often results from osteoporosis-related vertebral collapse or other causes. This has possible consequences on lung functions. Objective: To evaluate the effects of aging related loss of height to severity of dyspnea. Method: Patients visited pulmonary function test laboratoryat Baghdad teaching hospital outpatient clinic department from first of November 2009 to thirty first of December 2010 for preoperative assessment were recruited to participate in our study. All recruited subjects were evaluated with a clinical history and physical examination followed by measurements of arm span, standing height, weight, forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). Patients 40 years old of age and older were included .Patients with chronic disabilities (cardiac, respiratory or systemic diseases) were excluded. Patients were classified according to their gender and Medical Research Council severity of dyspnea. Results: one hundred thirty one subjects aged 40 years and older were recruited for this study. Arm span to height ratio was significantly negatively correlated with FEV1/FVC ratio, FVC, and positively correlated with severity of dyspnea. Conclusion:There is a significant association between increased arm span to height ratio with increased severity of dyspnea. The role of arm span measurements in assessment of pulmonary function tests in older patients and the association between loss of height and dyspnea deserves further evaluation.